2014
DOI: 10.1021/jp503177h
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Methanol Steam Reforming on Co(0001) and Co(111) Surfaces

Abstract: We report a periodic density functional theory (DFT) study of the methanol steam reforming (MSR) reaction on the Co(0001) and Co(111) surfaces. Thermochemistry and activation barriers for all elementary steps of two commonly accepted mechanisms, CH2O decomposition and H2COOH formation, were calculated along with the water gas shift (WGS) reaction. The adsorption energies on Co(0001) and Co(111) are within 0.05 eV for all the MSR intermediates examined, which suggests the same catalytic activity for both surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 62 publications
27
77
1
Order By: Relevance
“…A large adsorption energy of −5.81 eV (relative to O(g)) is obtained, consistent with previous theoretical values. 32,43 H*. H* binds strongly with three Co atoms at an fcc hollow site, yielding an adsorption energy of −2.62 eV, which is in accordance with the previous calculation values (−2.81 and −2.63 eV).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A large adsorption energy of −5.81 eV (relative to O(g)) is obtained, consistent with previous theoretical values. 32,43 H*. H* binds strongly with three Co atoms at an fcc hollow site, yielding an adsorption energy of −2.62 eV, which is in accordance with the previous calculation values (−2.81 and −2.63 eV).…”
Section: Resultssupporting
confidence: 91%
“…42 The adsorption energy for this species is about −3.46 eV, which is in excellent agreement with previous reports. 25,32,43 O*. The scission of the H−O bond in OH* produces adsorbed oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…We feel it is pertinent to mention a computational study of methanol steam reforming on Co(0001) and Co(111) surfaces by Luo et al to end the analysis of this section regarding computational breakthroughs in methanol decomposition [74]. Takewaza et al proposed that group VIII metals, such as Ni, Rh, Pd, or Pt, might favor methanol decomposition into CO against steam reforming into CO 2 , and though not included in the mentioned study, cobalt is a group VIII metal [77].…”
Section: Computational Results Iii: Non Ru-pt Pt and Ru Catalystsmentioning
confidence: 99%
“…Luo et al found that coadsorbed O and OH can promote O-H bond breaking or forming reactions and with the participation of O and OH, reaction barriers of all O-H bond breaking or forming can be reduced by 25%-90%. Further, conversion of CO to CO 2 on conversion of CO into COOH or CO 2 before desorption into CO(g) is competitive, and therefore the water gas shift may play also an important role [74].…”
Section: Computational Results Iii: Non Ru-pt Pt and Ru Catalystsmentioning
confidence: 99%
“…Thus, the fate of formaldehyde will be one of the following: (i) decomposition into HCO and H surface species (reverse of reaction 6a); (ii) desorption from the surface; or (iii) further reaction to other oxygenated compounds, e.g., formate, HCOO, species. However, based on the DFT computed barrier for the reverse of reaction 6a on Co(0001), i.e., 0.22 eV (0.13 eV with zero-point energy corrections) [70], formaldehyde desorption or further reaction to other oxygenated compounds seem difficult.…”
Section: Co* + H* → Coh* + * (3a)mentioning
confidence: 99%